Engineering Design for Aircraft-Based Observations of Typhoons - Wei Zhai; Chuanhai Qian; Hao Wu; Peitao Zhao; Shuo Fu; Yuedong Wang; Zechun Li (中国工程科学)
Typhoon is the most important disaster-causing weather system in the southeast coastal area of China during summer and autumn. Using aircraft as a mobile observation platform for direct observation of typhoons can obtain critical information about typhoons' environmental fields and their core structures, thus improving the accuracy of typhoon forecasts and warnings, as well as the effectiveness of disaster prevention and mitigation. Based on the typhoon observation practices using aircraft in China and abroad, this study proposes key considerations regarding the engineering design for aircraft-based observations of typhoons, encompassing aircraft selection, construction of support bases, airborne detection equipment, flight route planning, observation data transmission, and data application and evaluation. Furthermore, the following suggestions are proposed for establishing typhoon observation operations using aircraft in China: (1) building a professional typhoon observation command center, (2) promoting typhoon observation operations that combine manned aircraft with unmanned aerial vehicles, (3) conducting typhoon observation experiments with multi-platform coordination, (4) increasing stable support for aircraft-based typhoon observation projects, and (5) initiating an international major scientific program in the field of aircraft-based observations of typhoons.